Santri Waria Social Space: Study of the Phenomenon of Waria Al-Fatah Islamic Boarding School Yogyakarta - Isti’anah, Isti’anah; Wibowo, Safrudin Edi; Faizin, Khoirul (Borong Newinera Publisher, 2024)
This research is about how the social space of transvestite students towards the community around the Al-Fatah transvestite boarding school. The Al-Fatah transvestite boarding school is a very rare boarding school, where this transvestite boarding school contains special transvestite students who want to undergo their spiritual needs comfortably. Where transgender people always get discrimination due to their differences. In addition, we know that there are many transgender communities in Indonesia, but they mostly focus on health and HIV prevention. However, this transgender boarding school has a religious focus, besides that this transgender boarding school is one of the only ones in Indonesia, precisely in the city of Yogyakarta. This research focuses on how fellow humans respect and honor each other.